The Purpose and Function of Hadith on Economics from the Perspective of Islamic Education and Economics - Kamilatus Zahroh; Mohammad Fattah (Penerbit Hellow Pustaka, 2026)
Hadith is the second primary source of Islamic teachings after the Qur’an and holds a strategic position in shaping the Islamic economic system. Hadith not only functions as an explanatory source for Qur’anic verses that are general in nature, but also serves as a normative and practical guideline in regulating the economic behavior of Muslims. This article aims to analyze in depth the objectives and functions of hadiths related to economics, as well as their relevance from the perspectives of Islamic education and Islamic economics. This study employs a qualitative approach using a library research method, with data sources consisting of the Qur’an, authoritative hadith collections, scholarly journal articles, and books on Islamic economics, particularly the works of La Coy and Ahmad Mohammad Tidjani. The findings reveal that economic hadiths aim to uphold justice, prevent oppression and injustice in economic transactions, and shape economic ethics based on the values of honesty, trustworthiness, and social responsibility. In the context of Islamic education, economic hadiths function as a source of values in the formation of students’ economic character.